Strapping for temporomandibular joint dysfunction - Babu Abraham; John Sandhya; Unni Amith (Wolters Kluwer Medknow Publications, 2008)
Temporomandibular joint dysfunction (TMJD) is a common problem seen in many of the dental clinics. Management of this depends on an accurate diagnosis of the cause for the TMJD. Physical therapy and rehabilitation play a vital role in the management of these dysfunctions. Physical therapy is useful in treating post-traumatic stiffness of the TMJ while strapping of the TMJ for a dysfunction along with conventional physical therapy is of benefit in terms of reduction in click, decrease in pain, and an improvement in function.